Cheese Analogues, an Alternative to Dietary Restrictions and Choices: The Current Scenario and Future - Ingrid Leal; Paulo Correia; Marina Lima; Bruna Machado; Carolina de Souza (Foods, 2025)
The increasing demand for plant-based cheese alternatives reflects a shift toward healthier and more sustainable food choices. This study aimed to map technological trends, formulation strategies, and major challenges in the development of plant-based cheese analogues through a systematic review of the scientific literature and patents. Following the PRISMA protocol, searches were conducted in ScienceDirect and Lens.org between December 2024 and January 2025 using keywords related to cheese analogues. A total of 1553 scientific articles and 155 patents were initially retrieved. After applying inclusion and exclusion criteria, 88 articles and 66 patents were selected for detailed analysis. The results show a growing interest in this field since 2020, peaking in 2024. Data from 2025 may be limited due to the search period. Keywords were clustered into three main areas: (1) Formulation and Composition, (2) Texture and Processing, and (3) Food Safety and Consumer Acceptance. The United States leads in patent registrations (59). Valio Company and Cargill were the most active assignees, with nine and eight patents, respectively. This study highlights the importance of integrating food science and technology to improve the quality, sensory attributes, and market competitiveness of plant-based cheese analogues compared to traditional dairy products.